Disección aórtica. A propósito de un caso. Acute aortic dissection. Regarding a case. - Dr. Joel Brooks Tamayo; Dr. Oyantay Mérida Álvarez; Dr. Juan Carlos Valiente Reyes; Dr. Abel Yoandri Leyva Quert (ECIMED, 2010)
We report a patient with personal antecedents of arterial hypertension (Class II C) that enteredin the Hospital "Hermanos Ameijeiras" with a severe pain of sudden appearance in theanterior thoracic region and stabbing character that irradiated to the back. A transthoracicechocardiogram was performed, showing a very mobile intimal flap at the level of the aorticroot, extended until the abdominal aorta and the left renal artery, suggestive of dissection.The echocardiography is one of the more versatile non invasives techniques due to its clinicalapplications in the whole spectrum of the cardiovascular pathologies. It is quick, cheap,broadly available, it doesn't use contrast substances and is realizable in any dependence ofthe hospital, avoiding the transfer of the patient, habitually unstable. The patient receivedsurgical therapy and evolved satisfactorily.